Isolation of cellulolytic bacteria, including actinomycetes, from coffee exocarps in coffee-producing areas in Vietnam - Han B. Bui (International Journal of Recycling of Organic Waste in Agriculture)
Background Microorganisms have been used to decompose cellulolytic waste in agriculture for the past many years. However, much of the cellulosic waste including coffee exocarps which are wastes from raw coffee process in Vietnam is often disposed of by biomass burning and discharged into the environment in developing countries, thus causing considerable environmental pollution. Besides, these organic wastes decompose slowly when they are used to produce compost in ordinary conditions. Therefore, using microorganisms to manufacture natural compost from coffee exocarps is considered a useful and environmentally sound alternative. Results In the course of screening for cellulose-degrading bacteria and actinomycetes, 38 bacterial strains and 18 actinomycetes strains were isolated from 15 coffee exocarp samples in coffee-producing areas in Vietnam. The isolates grew with cellulose as the sole sources of carbon and energy. The results of cellulolytic activity determinations were that 13 bacteria ([34 %) and 10 actinomycetes ([56 %) showed enzymatic degradation of cellulose. The isolated strains were identified as belonging to members of the Genus Streptomyces, Actinomycetes, Clostridium and Bacillus. Cellulose-degrading ability of the isolated microorganism strains was mostly 96 % with filter paper; however, for coffee exocarps, it was considerably lower, only about 37 % of the cellulose was digested after 30 days of incubation to coffee exocarps. A medium containing rice husk powder and lactose with pH 7.0 positively affected the cellulolytic activity of A1 and A9 strains. Cellulolytic activity of B4 and B7 strains was also most appropriate when the medium contained peptone, CMC, and with a pH 7.0. Optimal temperature for actinomycetes and bacteria isolate strains was at 25â35 C. Conclusion We concluded that the cellulolytic bacteria and actinomycete could be isolated from coffee exocarps which are normally discharged into the environment in coffee-producing areas. These microorganisms could be used to decompose cellulosic wastes, making compost from coffee exocarps, which could be applied in agriculture in Vietnam and other developing countries.